2017
DOI: 10.2172/1607664
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of LED Street Lighting’s Impact on Sky Glow

Abstract: These resources included assistance and guidance writing scripts to execute the SkyGlow Simulator model along with the use of a supercomputer, Constance, and ultimately a Windows HPC cluster, housed at PNNL's headquarters in Richland, WA.  Ian Ashdown, President at by Heart Consultants, contributed an early model SkyGlowCalc and shared a significant amount of time and effort investigating not only the numerous models available but also the literature discussing the various impacts to sky glow.  Marc Ledbette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Although all LED lamps were assumed to emit only downwards, we have also introduced 5% uplight into the results presented in Figure 4 in order to simulate combined effect of fully shielded lights and incumbent luminaire distributions. The 5% uplight figure was chosen following the estimate of Kinzey et al [23] for "relatively poor drop-lens cobra head street lights." While F = 0% and low AOD is the condition most representative of the field skyglow measurements reported here, we varied both parameters.…”
Section: Results Of Model Runsmentioning
confidence: 99%
“…Although all LED lamps were assumed to emit only downwards, we have also introduced 5% uplight into the results presented in Figure 4 in order to simulate combined effect of fully shielded lights and incumbent luminaire distributions. The 5% uplight figure was chosen following the estimate of Kinzey et al [23] for "relatively poor drop-lens cobra head street lights." While F = 0% and low AOD is the condition most representative of the field skyglow measurements reported here, we varied both parameters.…”
Section: Results Of Model Runsmentioning
confidence: 99%
“…Similar concerns about the adverse effects of the rapid spread of full spectrum LED lighting are voiced by dark sky advocates (Bierman, 2012). The spectrum of light used will greatly affect the amount of scattering of light at different distances from a source (Kinzey et al, 2017). The extent of these effects depends in part on the spectral characteristics of the LEDs used, and many opportunities are available to evaluate the performance of the wide array of LED spectral configurations, such as investigating multiple spectral configurations of 2700 K LEDs to reduce attraction of flying insects (Longcore et al, 2015) or comparing LEDs of different color temperatures (Eisenbeis & Eick, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Such a switch can be catastrophic for the effects on other species, or it can be a benefit, depending on the spectrum, duration, direction, and intensity of the new lamps (Gaston et al, 2012;Longcore et al, 2015;Rodríguez, Dann, & Chiaradia, 2017a). The same applies to sky glow (Kinzey et al, 2017). Some ecologists have voiced generic concerns about LEDs in general, questioning whether they pose a risk across the board (Pawson and Bader, 2014;Stone, Jones, & Harris, 2012), and noting the unfortunate "rebound effect" in which more efficient lighting leads to deployment of even more light (Kyba et al, 2017;Kyba, Hänel, & Hölker, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This figure highlights potential disagreement between the metrics in the magnitude of impact that changing CCTs might have on circadian stimulus, depending on the location of the violet/blue peak in the source SPD. Given this potential effect, concerns have been raised regarding the impact of LED lighting on circadian rhythms, as stated in a recent USDOE fact sheet [39]. It suggested that chronic disruption of circadian rhythmicity by LED light sources has the potential to yield serious long-term health consequences, although there are no examples in any literature of such circadian disruption arising from the installation of LED public lighting [40].…”
Section: The Radiometric and Photometric Properties Of The Artificial...mentioning
confidence: 99%